Strategi Pengembangan Bisnis Usaha Mikro Kecil dan Menengah Angkringan Mas Ary - Vandana, Anggi Febri; Wijaya, Fanji (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The Indonesian business industry, especially MSMEs, is growing rapidly. With increasingly diverse consumer demands, business owners must change their strategies to maintain the continuity of their businesses and change their business models to suit progress. This is interesting research to study. Using SWOT model analysis, we can determine the potential and advantages of Angkringan Mas Ary to maintain the company. This research aims to find the methods needed for Angkringan Mas Ary. This research uses descriptive qualitative methodology. The research results show that the UMKM Angkringan Mas Ary already has eight business elements that must be considered when running a business, but there are still shortcomings in improving them. Primary data was obtained through documentation, observation and direct interviews with the owners and customers of Angkringan Mas Ary